2018
DOI: 10.2174/1871527317666171213154749
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of ω -3 Fatty Acids and Nano-Curcumin Supplementation on Intercellular Adhesion Molecule-1 (ICAM-1) Gene Expression and Serum Levels in Migraine Patients

Abstract: Considering the results of supplementation with omega-3 fatty acids plus curcumin led to reductions of both attack frequency and ICAM-1 serum level in patients, it seems that supplementation with these two nutrients not only can lead to improvements in the function of metabolic pathways, but can also be used effectively as a treatment or prevention of migraine complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 0 publications
1
37
0
1
Order By: Relevance
“…Each of the ω-3 or nanocorcinoma placebo were similar in color, shape and size and were synthetized by the related pharmaceutical company. The duration of treatment was two months [31].…”
Section: Patients and Supplementationmentioning
confidence: 99%
“…Each of the ω-3 or nanocorcinoma placebo were similar in color, shape and size and were synthetized by the related pharmaceutical company. The duration of treatment was two months [31].…”
Section: Patients and Supplementationmentioning
confidence: 99%
“…11 In a clinical trial, nanocurcumin plus omega-3 fatty acids supplementation have been shown to reduce both the attack frequency and the ICAM-1 (adhesion molecule associated with inflammation) serum level in patients with migraine. 12 Therefore, nanoformulations of curcumin have been developed for their superior therapeutic efficiency in inflammatory and oxidative stress processes. 13,14 The serotoninergic system represents one of the most important pathophysiological mechanisms of migraine; 5-hydroxytryptamine1 (5-HT1) receptor agonists are known to be effective in the treatment of migraine attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Combining fish oil with curcumin for additional benefits is a very new approach; clinical trials are limited, with inconsistent results [ 14 , 26–28 ], and effects on OA pain relief have not yet been tested. In migraine patients, fish oil and curcumin were found to have synergistic effects on reduction of inflammatory markers [ 26 , 27 ] and migraine attack frequency [ 27 ]. However, in people at high risk of developing type 2 diabetes, the combination did not result in any complementary effects on glycaemic control and blood lipids [ 28 ], and in our study we did not find any synergistic effects on cardiometabolic risk factors and cerebrovascular function [ 14 ].…”
Section: Discussionmentioning
confidence: 99%